2016
DOI: 10.21037/tlcr.2016.09.05
|View full text |Cite
|
Sign up to set email alerts
|

Are immune checkpoint blockade monoclonal antibodies active against CNS metastases from NSCLC?—current evidence and future perspectives

Abstract: Brain metastases occur in approximately half of patients with non-small cell lung cancer (NSCLC) and are associated with a poor prognosis and an inferior quality of life. Historically systemic therapy has had a limited role in CNS disease with a reliance placed on local treatments. The emergence of targeted therapies and immune checkpoint inhibitors (ICIs) in recent years has dramatically changed the treatment landscape of NSCLC. Programmed cell death-1 (PD-1) inhibitors have demonstrated efficacy in three ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…This organ-specific response may be the result of the different PD-L1 expression, microenvironment and genetic heterogeneity profiles between primary and metastatic sites. Many retrospective analyses on NSCLC and melanoma patients with liver metastases, treated with ICIs, experienced notably poorer response rates and survival outcomes [30,31]. The liver is characterized by an immune-suppressive microenvironment where IL-10-secreting dendritic cells, Kupffer macrophages and sinusoidal endothelial cells may induce T-cell anergy and decreased likelihood of response to immunotherapy alone [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This organ-specific response may be the result of the different PD-L1 expression, microenvironment and genetic heterogeneity profiles between primary and metastatic sites. Many retrospective analyses on NSCLC and melanoma patients with liver metastases, treated with ICIs, experienced notably poorer response rates and survival outcomes [30,31]. The liver is characterized by an immune-suppressive microenvironment where IL-10-secreting dendritic cells, Kupffer macrophages and sinusoidal endothelial cells may induce T-cell anergy and decreased likelihood of response to immunotherapy alone [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed the negative prognostic role of liver metastases, while the survival impact of bone and brain metastases remains still uncertain. Brain metastases are not confirmed as a negative prognostic factor because ICIs may cross the blood-brain barrier and induce disease response in selected patients [31]. Data from both retrospective series [36] and clinical trials showed good activity of ICIs as a single agent [37] or in combination with chemotherapy [38] in patients with brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Whether ICPis affect brain metastasis remains unclear (6,7). Some prospective trials are currently being conducted, and the results of a phase 2 trial of pembrolizumab for melanoma and NSCLC with brain metastasis (8) indicate that the brain lesions were responsive in 6 of 18 patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches may also lead to the development of small molecule ICI approaches that can penetrate the blood brain barrier (BBB), enabling ICI to be applied to primary brain cancer or brain metastases that are not amenable to treatment with current antibody-based ICI therapies. (14)…”
Section: Small Molecules the Next Generation Immune Checkpoint Inhibmentioning
confidence: 99%